Changing pattern of acute intestinal obstruction in Accra. - Naaeder, S. B.; Archampong, E. Q. (My University, 1993)
Five hundred and fifty-two cases of intestinal obstruction were seen over a two year period, January 1987 to December 1988. Strangulated external hernias and adhesions still remain the most common causes of intestinal obstruction in Accra, but there has been a change in their relative incidence with external hernias falling to 59.8 per cent and adhesive obstruction increasing to 21.0 per cent. There has been no change in the overall mortality and mortality from inguinal hernia which are still 9.4 per cent and 4.9 per cent respectively. However, there has been a significant improvement in mortality rate from volvulus and a slight improvement in mortality from adhesive obstruction even though the overall resection rate has increased from 12.7 per cent to 17.6 per cent.
Keywords: EMTREE medical terms: abdominal tumor; acute disease; adolescent; adult; age; aged; article; child; epidemiology; female; Ghana; human; incidence; infant; inguinal hernia; intestine obstruction; male; mortality; preschool child; prospective study; sex difference; umbilical hernia